Link between embryonic stem cell pluripotency and homologous allelic pairing of Oct4 loci. (2nd October 2017) - Asaka, Masamitsu N.; Uranishi, Kousuke; Suzuki, Ayumu; Hirasaki, Masataka; Nishimoto, Masazumi; Okuda, Akihiko
Abstract : The Oct4 gene is a master regulator of the pluripotent properties of embryonic stem cells (ESCs). Recently, Oct4 loci were shown to frequently localize in close proximity to one another during the early stage of cellular differentiation, implicating this event as an important prerequisite step for ESCs to exert their full differentiation potential. Although the differentiation capacity of embryonal carcinoma cells (ECCs), such as F9 and P19 ECC lines, is severely restricted compared with ESCs, ECCs bear a highly similar expression profile to that of ESCs including expression of Oct4 and other pluripotency marker genes. Therefore, we examined whether allelic pairing of Oct4 loci also occurs during differentiation of F9 and P19 ECCs. Our data clearly demonstrate that this event is only observed within ESCs, but not ECCs, subjected to induction of differentiation, indicating transient allelic pairing of Oct4 loci as a specific feature of pluripotent ESCs. Moreover, our data revealed that this pairing did not occur broadly across chromosome 17, which carries the Oct4 gene, but occurred locally between Oct4 loci, suggesting that Oct4 loci somehow exert a driving force for their allelic pairing. Abstract : Figure 5A shows transient homologous pairing of Oct4 alleles, but not Fshr alleles, of chromosome 17 in differentiation‐induced mouse embryonic stem cells.